(untitled) (Journal of the College of Education for Women, 2019)
Harold Pinter was one of the most important dramatists in the modern and thecontemporary age. Pinter presented his own dramatic realm in which he turns the theatre intoa moral institution. He employed the elements of several schools of drama and manipulatedthem in order to deliver his ethical messages emphasizing the necessity to regain and renewthe world’s morality in order to face the political and social injustices committed againsthumanity. His writings developed over more than fifty years in style, techniques and hisinterests. However, his main concern was his social and political satire.